2019
DOI: 10.1002/pros.23867
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast as a critical stromal cell type determining prognosis in prostate cancer

Abstract: Background Tumor stroma associates with prostate cancer (PCa) progression, but its specific cellular composition and association to patient survival outcome have not been characterized. Methods We analyzed stromal composition in human PCa using multiplex immunohistochemistry and quantitative, high‐resolution image analysis in two retrospective, formalin‐fixed paraffin embedded observational clinical cohorts (Cohort I, n = 117; Cohort II, n = 340) using PCa‐specific mortality as outcome measurement. Results A h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…1b), we performed a new genomewide analysis to identify specific regions of differential methylation. We excluded the three patients (patients 1-3) previously analysed with WGBS [21]. This revealed 50,000 significantly differentially methylated positions (DMPs) between CAFs and NPFs (Fig.…”
Section: Identifying Novel Differentially Methylated Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b), we performed a new genomewide analysis to identify specific regions of differential methylation. We excluded the three patients (patients 1-3) previously analysed with WGBS [21]. This revealed 50,000 significantly differentially methylated positions (DMPs) between CAFs and NPFs (Fig.…”
Section: Identifying Novel Differentially Methylated Regionsmentioning
confidence: 99%
“…The functions of CAFs also evolve with cancer progression [14][15][16][17]. Indeed, changes in the histopathological features, gene expression profile and length of telomeres in the stroma have all been associated with poorer relapse-free or overall survival of men with prostate cancer [14,15,[17][18][19][20][21]. The phenotype of CAFs is also enduring and does not rely on continuous interactions with epithelial cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…CAFs have an active role in mutual bidirectional interactions with tumor cells and other cell types in the TME, thereby promoting the niche that allows the tumor and promoting tumor development. Increasing studies have indicated that CAFs can be utilized as a significant prognostic marker in various tumors . Since TANs are the most common infiltrated type of immune cells in GAC, there may exist a forceful mutual effect between GAC‐derived CAFs and invasive TANs.…”
Section: Introductionmentioning
confidence: 99%
“…CD4 and CD8 T cells produce tumor-promoting cytokines and Treg lymphocytes suppress anticancer immune response [57,58]. PC enriched in stroma with a high number of fibroblasts was found to be more aggressive and androgen-resistant [8]. Study on PC xenografts distinguished a stromal-derived metastatic gene expression signature, which can be used to separate indolent PC from tumors with metastatic potential [59].…”
Section: Pc Stroma and Its Neural Componentmentioning
confidence: 99%
“…Consequently, this phenomenon has been incorporated into the "hallmarks of cancer" [5,6]. Stroma can have suppressing and/or promoting effects in solid tumors and also hematogenic neoplasms [7,8]. TME consists of the extracellular matrix (ECM) composed of DOI: 10.1159/000505437 structural, specialized proteins (collagen, elastin, fibrilin, fibronectin elastin) and stromal cells such as cancer-associated fibroblasts (CAF), specialized mesenchymal cell types (adipocytes, myogenic cells), mesenchymal stem cells, immune cells, endothelial cells as well as extravasated blood cells [2,9].…”
Section: Introductionmentioning
confidence: 99%